2022
DOI: 10.1371/journal.pone.0261304
|View full text |Cite
|
Sign up to set email alerts
|

The role of online social networks in improving health literacy and medication adherence among people living with HIV/AIDS in Iran: Development of a conceptual model

Abstract: Online social networks have been used to enhance human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) prevention, diagnosis, and treatment programs worldwide. This study aimed to develop a conceptual model of using online social networks in improving health literacy and medication adherence among people living with HIV/AIDS in Iran. This mixed-method sequential exploratory study was conducted in three phases. Firstly, a series of semi-structured interviews with a purposive sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Adequate social support can be obtained from families, friends, peers, health care professionals and organizations, even from internet, which has been shown to improve medication adherence and the quality of patients' lives [ 32 34 ]. Herein, we found that that social support was directly associated with medication adherence, which is similar to the results from previous studies [ 9 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adequate social support can be obtained from families, friends, peers, health care professionals and organizations, even from internet, which has been shown to improve medication adherence and the quality of patients' lives [ 32 34 ]. Herein, we found that that social support was directly associated with medication adherence, which is similar to the results from previous studies [ 9 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of men aged 15 and over living with HIV was estimated at 43,000 [23,000– 91,000], while that of women stood at 16,000 [8800–32,000] [ 3 , 4 ]. Injection drug use is considered the main cause of HIV transmission in Iran [ 5 ]. According to a previous study, there were about 230.000 people injecting drug in Iran in 2016 [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, female sex workers are considered the second most at risk population for HIV transmission [ 13 ]. As prostitution and sex work are illegal and extremely stigmatized in Iran [ 14 ], it has affected the process of diagnosis and treatment of HIV/AIDS adversely and consequently has posed major challenges to cope with it in Iran [ 5 , 15 ]. To encourage safe sexual behaviors and control spread of HIV/AIDS in this part of population, other centers so-called “Vulnerable Women’s Counseling Centers” were created separately to provide counseling services, and distribute preventive and protective services for female at the risk of getting HIV (women live with HIV/AIDS use their curative services from BDCCs).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations